Integration of Computational Thinking in GeoGebra-Assisted Measurement Learning on Mathematical Problem Solving Skills - Izza, Kuni Kumala; Noening Andrijati (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
Solving math puzzles is one of the most essential skills students should have in the 21st century. Despite this, Indonesian students' problem-solving ability still needs to improve. This research aims to analyze the effect of integrating computational thinking in geogebra-assisted measurement learning on mathematical problem-solving skills. This research uses a quantitative approach with an experimental type. The sample for this research consisted of 45 elementary school students using simple random sampling techniques. The methods used to collect data are observation and tests. The instrument used to collect data is test questions. The techniques used to analyze data are quantitative analysis and inferential statistics. The results showed that there was variation in the ability of the experimental and control groups to solve mathematical puzzles. The t-test results show an average difference between the pretest and post-test results in the control and experimental classes. There is a significant difference in problem-solving abilities between students who take part in learning using the computational thinking approach assisted by Geogebra and students who take part in learning without the computational thinking approach assisted by Geogebra. It was concluded that learning using a computational thinking approach assisted by Geogebra can improve problem-solving abilities.